Organizational Resources, Networking Resources, Marketing Capabilities And Export Performance: Evidence From Thai Agro-Based Firms - Tooksoon, Phadett (2010)

(untitled)
The Thai economy is very dependent on the agro-based sector. The availability of abundant resources has enabled firms in this sector to play a fundamental role in the economic development and employment for the population. This study is undertaken to identify the competitive strengths of firms in the agro-based sector and their export performance. The resource-based view and the social capital theory provide inputs into the research framework. It is proposed that organizational resources comprising of reputation resources, financial resources, human resources, and research and development and technology resources contribute positively to the firm’s export performance.